A Relatively Complete Description of the Out-coupling Limitation for Planar OLEDs - Mongelli, Guy Francis (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2019)
Within this work the computation to describe the out-coupling efficiency limitation of a classical OLED structure is detailed. This manuscript takes a classical geometrical optics approach, combined with fundamental integral calculus. Several specific cases are developed with numerical results. This model looks at the geometrical optics surrounding total internal reflection, including: defining the critical angle, considering the luminous flux distribution at various angles of incidence, and considering the critical angle different materials make with organic layers, ITO, SiNy and air. The critical angles made with typical organic compounds are also studied.